Variation for health-enhancing compounds and traits in onion (Allium cepa L.) germplasm - Insani, Ester Marina; Cavagnaro, Pablo; Salomon, Virginia María; Langman, Leandro Ezequiel; Sance, María; Pazos, Adriana Alejandra; Carrari, Fernando; Filippini, Olga; Vignera, Laura; Galmarini, Claudio Romulo (2017)
Consumption of onion has been associated with reduced incidence of chronic diseases. Phenolic, organosulfur and carbohydrate compounds present are largely responsible for these effects. This study examined compositional variation for health-enhancing compounds in a genetically diverse collection of onion cultivars. Total antioxidant activity and aroma profiles were characterized. Significant variation in bulb concentration for total and individual phenolic compounds, thiosulfinates, carbohydrates, and total and soluble solids was found. The range of variation was particularly large (>50-fold difference between the cultivars with the highest and lowest content) for fructo-oligosaccharides (FOS) and the polyphenols quercetin, epigallocatechin gallate and epicatechin gallate. Amino acid profiles varied significantly as well with substantial variation (~10 fold) observed in both total and essential amino acids. Total antioxidant activity was positively correlated with polyphenols content, and quercetin in particular (r = 0.83), suggesting a major contribution from phenolic compounds to onion antioxidant properties. Significant positive correlation was also found between solids and thiosulfinates content (r = 0.74) and between solids and FOS (r= 0.81), suggesting a dilution/concentration effect for organosulfur compounds and FOS in onion bulbs. The present study revealed broad variation for health-enhancing compounds content in onion germplasm, which can be exploited in breeding programs aiming at increasing onion nutraceutical value.